Pakan Sapi Perah Laktasi di Peternakan Rakyat di Desa Bawang Kotamadya Kediri: PFH Lactation Dairy Cattle Feed at People’s Farm in Bawang Village, Kediri Municipality - Purwanti, Purwanti; Hastiningtyas, Ermi (Jurnal Riset Agribisnis dan Peternakan, 2023)
Dairy cows cultivated by smallholder farmers have the disadvantage of providing rations. The ration given is the feed available around without calculating the nutritional value. The purpose is to know the quantity and quality of rations of lactation PFH dairy cows. The results showed that the consumption of eating substances exceeded the needs, namely the consumption of kerin materials (BK) and protein digestibility (DP), while the lower than the needs were the total digestible food substances (TDN). The average consumption of BK, DP and TDN consumed by the record per day was 12.60 kg, 970.43 g and 4.72 g. The balance of forage and concentrates in the ration given by PFH lactation dairy cows was 37.5: 62.5. The milk production of dairy cows PFH lactation is 9.5-12.5 liters with a fat content of 3.2 percent. It is recommended in the preparation of the ration of lactation dairy cows based on body weight, amount of production and fat content, so that the feed given is efficient and economical, but optimal production can be obtained.